Ethical Stock Portfolios : Does It Have High Risk and Low Return - Kewal, Suramaya Suci; Putranto, Yohanes Andri (Jurnal Economia, 2023)
This study examines the comparison of stock performance as measured using the return and risk of stock portfolios of ethical and non-ethical companies on the Indonesia Stock Exchange. Portfolio formation using a single index model during 2016-2019. The data analysis technique uses an independent sample t-test with a significance level of 5%. The results showed that there were no differences in portfolio return and risk. The average portfolio return is 0.22% for ethical stocks and 0.27% for non-ethical stocks. There is also no significant difference in portfolio risk, 0.87% for ethical stock portfolios and 0.99% for non-ethical stocks. This research has implications for investors who are interested in ethical stocks where they don't have to worry about high portfolio risk and low returns because the results show that the SRI KEHATI index stock portfolio provides the same level of risk and return as the LQ45 index stock portfolio.